Tax evasion and illicit cigarettes in California: prevalence and demand-side correlates - Prieger, James E. (Crime, law and social change, 2022)
Unlike some areas of crime, participation in illicit tobacco markets is not rare and spans most sociodemographic groups. Measurement of the scale of illicit trade in cigarettes usually is for markets with recently increased (or continually increasing) excise taxes. This study examines survey data from adult cigarette smokers in California at a time when prices and taxes had been fairly stable for many years. Even with no recent price shocks in the market, the results indicate that one-third of cigarette packs may lack a valid tax stamp and that between 18 and 25% of smokers avoided taxes by bringing cigarettes into the state from elsewhere in the past month (36% in the past year). Over 10% of packs were purchased for a suspiciously low price and 24-32% of smokers think they might have bought untaxed cigarettes in the past month. Furthermore, 20% think they may have consumed counterfeit cigarettes in the past month. There is a low incidence of illegal sales of single cigarettes. Men, smokers who roll their own cigarettes, e-cigarette users, younger smokers, and those with more income and education are all more likely to engage in at least some of the suspect market behaviors examined. The results show that many smokers from all segments of society participate in the illicit market for cigarettes - wittingly or not - which complicates efforts to reduce illicit trade.